THE INFLUENCE OF SERVICE MARKETING MIX TO SATISFACTION OF STUDENTS AT CHARITY HIGH SCHOOL TOMOHON - Benua, Deilvia C.; Tewal, Bernhard; Sumarauw, Jacky (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Nowadays, education has a significant meaning. Education supports and has a function of enhancing human quality. The business owners have seen this as an opportunity to build private schools. Having built these schools, they need to know the right strategy to meet its customers? satisfactions. The purpose of this study was to determine the influence of marketing mix such as product, price, promotion, place, people, physical evidence, and process for student satisfaction. The place of research is in Tomohon Caritas Catholic High School. The population is 284 students and the sample taken is as many as 100 samples. The analytical method used is the Multiple Regression, while validity and reliability tests are also used. This research can be categorized into quantitative descriptive research. The result shows that as for the t-test, the variables product, price, place people and physical evidence, individually as well as partially is significant influence toward students? satisfactions of Charity Catholic high school students in Tomohon. On the other hand, the variables promotion and the process, individually as well as partially, is not significantly influence toward students? satisfactions of Charity Catholic high school students in Tomohon. The management of Charity Catholic high school needs to improve and focus its marketing strategies on marketing mix strategy with respect to the education quality of the school, in detail such as teachers? attentions and learning process. Keywords: services marketing mix, student satisfaction